STUDY ON TEACHER DISCOMFORT AT A TECHNOLOGICAL UNIVERSITY IN FORTALEZA - Vieira, Maria Lenilce Gonçalves; Antônio, Ana Sofia (Seven Editora, 2026)
The concept of malaise is used to highlight negative implications that affect teachers' behavior as a result of the psychological and social conditions in which they practice their profession. It constitutes a constant concern regarding the health and illness of teachers who are part of a complex process: well-being, and malaise is related to daily school life. The physical facilities of a classroom can interfere with the well-being of teachers and, naturally, that of students.Using a quantitative methodology, 80 engineering professors at IFCE were surveyed. They responded to a questionnaire and demonstrated that their level of physical and mental fatigue is worrying, along with discouragement, anguish, and stress related to their work. It is recognized that the obstacles can be enormous, as the school's very structure, as well as its pedagogical and educational situation, require reform. It is believed that only a new, critical and sensitive perspective can benefit teachers. Therefore, something must be done to promote teacher well-being and disseminate this knowledge to the academic community and the entire educational community.